Improved control of energy consumption by a photovoltaic system equipped with a storage device to meet the needs of a local facility - Shavolkin, Olexander; Shvedchykova, Iryna; Jasim, Jasim Mohmed Jasim (Eastern-European Journal of Enterprise Technologies, 2021)
This paper has considered improving the management of energy consumption by a photovoltaic system with a storage device for a local object connected to the network. The aim of the study is to reduce expenditures when paying for electricity consumed from the network, when loading an object, independent of the time of year, and to eliminate energy generation to the grid. An energy generation control algorithm has been improved whereby the state of battery charge during the day is based on a forecast. That could reduce electricity consumption at night with better utilization of rechargeable battery and photovoltaic battery power during the day. It is proposed to use autonomous operation by disconnecting from the network during peak tariff hours and during the day with enough energy generation by a photovoltaic battery. This would ensure the normal functioning of an object in the event of a possible deterioration in the quality of voltage in the network while reducing the loss of energy in the inverter. Predictive control of the expected battery charge at the next checkpoint (at 0.5 hours or less between control points) has been proposed. A control system structure has been developed whereby a rechargeable battery current is set depending on an operational mode, the tariff zone, and the projected generation by a photovoltaic battery while reducing the modulation frequency under an autonomous mode. In this case, the modes are switched and the structure is changed taking into consideration the state of battery charge. Simulation in the daily cycle has shown the possibility of reducing the cost of electricity consumed from the network by 1.7‒8 times at two or three tariff rates. Simulation of electromagnetic processes in the system confirms acceptable regulation indicators when switching the structure, as well as a decrease in the energy loss in an inverter under an autonomous mode by up to 40 %